2012
DOI: 10.2134/agronj2011.0358
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Pedigree, Historical Data, Dominance, and Data Unbalance for Selection Efficiency

Abstract: Th e objective of this study was to assess the impact of pedigree, historical data, dominance, and data unbalance on the estimation and precision of genetic variances and breeding values and on the selection effi ciency in annual crop breeding. Expansion volume and grain yield from 12 trials of inbred progeny and four tests of non-inbred families were used in the analyses. Th e S 1 to S 5 progeny trials were designed as incomplete blocks, the S 6 progeny trials were designed as complete blocks, and the half-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
2
0
2
Order By: Relevance
“…We have chosen to adopt the MTME model for the inbred lines selection since a combined analysis takes more data into consideration and consequently is often more accurate to predict breeding values than single models [ 37 , 38 ]. According to [ 39 ], the increase in accuracy with the use of multi-trait best linear unbiased prediction (BLUP) analysis compared with single-trait analysis is proportional to the difference between the genetic and environmental correlations of the analyzed traits.…”
Section: Resultsmentioning
confidence: 99%
“…We have chosen to adopt the MTME model for the inbred lines selection since a combined analysis takes more data into consideration and consequently is often more accurate to predict breeding values than single models [ 37 , 38 ]. According to [ 39 ], the increase in accuracy with the use of multi-trait best linear unbiased prediction (BLUP) analysis compared with single-trait analysis is proportional to the difference between the genetic and environmental correlations of the analyzed traits.…”
Section: Resultsmentioning
confidence: 99%
“…Portanto, quando se consideram condições experimentais limitantes, ou na seleção de multicaracterísticas, o emprego de modelos mistos com informação de parentesco pode ser o mais recomendado (Viana et al, 2010b(Viana et al, , 2012. Em termos práticos, a manutenção do registro de genealogias para progênies em teste pode demandar maior esforço, o que influencia a opção do uso destas informações na seleção.…”
Section: Resultsunclassified
“…Entretanto, no melhoramento de espécies anuais, seu uso não é tão frequente, embora haja um número crescente de relatos, em diferentes espécies, como milho (Viana et al, 2010a(Viana et al, , 2011(Viana et al, , 2012, feijão (Baldissera et al, 2012), arroz (Borges et al, 2012) e trigo .…”
Section: Introductionunclassified
“…When using trials with unbalanced data, or just a sample of the cultivars, the prediction accuracy estimates tend to be lower, and the model may not be efficient in evaluating the performance of the cultivars [ 72 , 73 ]. Viana et al [ 74 ] working with unbalanced data, showed that the lack of data resulted in relevant effects on the estimation of genetic variances, the accuracy of prediction and the ranking of predicted genetic values, which can affect the efficiency of selection.…”
Section: Discussionmentioning
confidence: 99%